2013
DOI: 10.1016/j.juro.2012.11.023
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Institutional Evaluation of Active Surveillance for Low Risk Prostate Cancer

Abstract: Purpose-For select men with low-risk prostate cancer, active surveillance (AS) is more often being considered a management strategy. In a multicenter retrospective study we evaluated the actuarial rates and predictors of remaining on AS, incidence of cancer progression, and pathologic findings of delayed radical prostatectomy.Methods-A cohort of 262 men from four institutions met the following inclusion criteria: age ≤75, PSA ≤10 ng/ml, clinical stage T1-T2a, biopsy Gleason sum ≤6, ≤3 positive cores at diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
1
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 21 publications
4
64
1
6
Order By: Relevance
“…This is consistent with data from Europe [20] and the USA [22]: in these studies, the distribution to RP, RT, HT and 'other' therapies was 48.0, 45.2, 1.5 and 5.3%, respectively, and 60.5, 30, 7 and 2.5%, respectively. By contrast, Klotz et al [28] found the use of RT was predominant at 67% (RP, 26%; HT, 7%).…”
Section: Totalsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with data from Europe [20] and the USA [22]: in these studies, the distribution to RP, RT, HT and 'other' therapies was 48.0, 45.2, 1.5 and 5.3%, respectively, and 60.5, 30, 7 and 2.5%, respectively. By contrast, Klotz et al [28] found the use of RT was predominant at 67% (RP, 26%; HT, 7%).…”
Section: Totalsupporting
confidence: 91%
“…Most clinical studies mention T1c and T2a tumours almost exclusively. T1a/b cancer is either not included in the reports, not specified separately or represented only sparingly [20][21][22], e.g. 4.8% in the report by Klotz et al [8].…”
Section: Discussionmentioning
confidence: 99%
“…10,11,19,24 Fewer cohorts reportedly have a median followup of beyond 5 years. 5e7 Our results extend the median followup previously reported in this cohort from 3.6 to 5 years and include more than 200 men with followup beyond 7.5 years.…”
Section: Discussionmentioning
confidence: 99%
“…27 Along with clinical TNM stage and preoperative PSA value, Gleason score based on biopsy is among the most important factors in treatment decision making for prostate cancer. 13,[17][18][19][20] The AJCC 6th and 7th editions both state that prostate cancers should be microscopically diagnosed. Therefore, theoretically nearly every case should have Gleason patterns (SSF7) and/or scores (SSF8) recorded.…”
Section: Discussionmentioning
confidence: 99%
“…24 Several studies have explored the value of using the number of positive biopsy cores to enhance prediction of clinically insignificant disease or recurrence, with mixed results. 13,30 Inclusion of the number of positive and negative cores enhanced the predictive accuracy of a preoperative nomogram predicting the 10-year probability of prostate cancer recurrence after radical prostatectomy. 31 The AJCC 7th edition recommended as clinically significant collecting both the number of cores positive for cancer (SSF12) and the number of cores examined (SSF13).…”
Section: Discussionmentioning
confidence: 99%